2014
DOI: 10.14411/eje.2014.088
|View full text |Cite
|
Sign up to set email alerts
|

Consequence of the transformation of a primeval forest into a managed forest for carabid beetles (Coleoptera: Carabidae) - a case study from Białowieża (Poland)

Abstract: A comparison was made of the number of species, species diversity and ecological traits of carabid beetle (Coleoptera: Carabidae) assemblages inhabiting Białowieża Primeval Forest (National Park) and adjacent managed Białowieża forest planted following clear-cutting of the primeval forest 80 years ago. Five pitfall traps were set in each plot in the primeval and managed forests in areas that differed in terms of humidity and soil fertility. The first hypothesis tested was that the type of stand (primeval vs. m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 49 publications
2
20
0
Order By: Relevance
“…This species is abundant in the forests of South Moravia (Šejnohová, 2006). The species dominates in the forests of Poland (Sklodowski, 2006(Sklodowski, , 2014Kwiatkowski, 2011;Sklodowski & Garbalinska, 2011;Zalewski et al, 2012). There numerous reports of finding this species in Lithuania (Tamutis et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…This species is abundant in the forests of South Moravia (Šejnohová, 2006). The species dominates in the forests of Poland (Sklodowski, 2006(Sklodowski, , 2014Kwiatkowski, 2011;Sklodowski & Garbalinska, 2011;Zalewski et al, 2012). There numerous reports of finding this species in Lithuania (Tamutis et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The key filter condition could be high humidity and/or a low temperature, as both are among the most important environmental parameters influencing spatial distribution and persistence of not only the ground beetle adults, but especially the larvae that have limited mobility, weak chitinization, and therefore narrower tolerance limits than adults (Lövei & Sunderland, 1996). Another key factor for filtering co-existing species in the forest edge and interior could be the thick leaf litter layer, as it offers prey, habitat space and shelter from adverse microclimatic conditions (Koivula et al, 1999;Magura et al, 2001;Taboada et al, 2004;Skłodowski, 2014). While environmental filtering acted on ground beetles at the studied forest edge, in the case of nonvolant small mammals in southern Brazil, phylogenetically similar species coexisted less often than expected by chance, indicating a repulsion pattern (Luza et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Carabid beetles respond to changes in forest brought about by ecological succession. It has been demonstrated that the proportion of late-successional species in the carabid fauna is higher in stands with a more complex vertical structure growing on fertile soils compared to one-storied stands on poor soils (e.g., Skłodowski 2014). However, there have been no studies of carabid beetles in stands growing on poorer substrates where understory and a second story were introduced.…”
Section: Introductionmentioning
confidence: 99%